Winning the 3-Legged Race : When Business and Technology Run Together. - Hoque, Faisal; Zmud, Robert; Sambamurthy, V.; Friedman, Laurie B., 1964-; Wilson, Carl (Prentice Hall [Imprint] Prentice Hall PTR Pearson Education [distributor], 2005)
Annotation